Exploring user profiles and preferences for mobile apps promoting active lifestyles during pregnancy and postpartum: cross-sectional study - Laura Alves; Cátia Ferreira; Cristiana Mercê; Rita Santos-Rocha (BMC Pregnancy and Childbirth)
Abstract Background The proliferation of mobile health applications (apps) presents promising opportunities for promoting maternal-fetal health outcomes. While numerous pregnancy-related apps exist, their alignment with user needs and evidence-based recommendations remains understudied. This study aimed to analyze the usage profile, characteristics, and preferences regarding mobile apps for promoting a healthy lifestyle during pregnancy and postpartum, with particular emphasis on physical activity. Methods A cross-sectional retrospective study was conducted using a questionnaire titled “Active Pregnancy App– Promoting an active and healthy lifestyle during pregnancy and postpartum,” consisting of 36 questions in digital format via the Google Forms platform. The participants included 235 pregnant or postpartum women, with a mean age of 36 ± 4.67 years, with babies born between 2021 and 2023. Results Among the women surveyed, 80% engaged in physical activity during pregnancy (39% 1–2 times/week), and 63% in the postpartum period. Walking was the predominant activity (90% of health/wellness activities). Most participants (87%) had never used pregnancy-specific fitness apps, despite 53% using general fitness apps. The majority considered the existence of a specific application for physical activity during pregnancy and postpartum to be important or very important. The main preferences regarding the app were: access to recommendations on an active and healthy lifestyle during pregnancy and postpartum; direct interaction with health and exercise professionals; the ability to record health and clinical parameters, physical activity, and training logs; access to guidelines on postpartum preparation and recovery programs; and workouts to perform at home and outdoors. Conclusions User perspective is an actual trend for focusing on end users’ point of view and preferences, as they are the people for whom the software is designed. The results reinforce and highlight the relevance of building a specific app for physical activity and other lifestyle parameters during pregnancy and postpartum that includes reliable and updated information, allows interaction with health and exercise professionals for monitoring, and enables the recording of progress. These results will be used in the creation and development of the “Active Pregnancy App” which can thus better meet the needs and demands of pregnant and postpartum women.